163 BOOSTER SURFACTANT THERAPY BEYOND THE FIRST WEEK OF LIFE IN VENTILATED EXTREMELY LOW GESTATIONAL AGE NEONATES. (1st January 2006) - Merrill, J. D.; Ballard, P. L.; Hibbs, A. M.; Godinez, R. I.; Godinez, M. H.; Luan, X.; Ryan, R.; Reynolds, A. M.; Hamvas, A.; Spence, K.; Courtney, S.; Posencheg, M.; et al.
Abstract : Many extremely low gestational age neonates (≤ 28 wk, ELGANS) continue to require intubation and mechanical ventilation beyond the first week of life and many experience episodes of dysfunctional surfactant associated with low surfactant protein B content and clinically significant respiratory decompensations (Pediatr Res 2004;56:918-26). We hypothesized that booster surfactant treatment (booster) given during week 2-3 to these infants is safe and improves pulmonary outcome. Infants were enrolled in one of two booster pilot trials. ELGANS requiring ventilation at 7 to 10 days of life received one to two doses of "prophylactic" surfactant (Infasurf®, 3 mL/kg) 1 week apart. In a separate "Rescue" pilot trial, ventilated ELGANS at 5 to 21 days of life with respiratory decompensation received two doses of Infasurf over 12 to 24 hours. Tracheal aspirate (TA) samples were analyzed for minimum surface tension (STmin) in a pulsating bubble surfactometer and for concentrations of cytokines, growth factors, and chemokines. Clinical data including respiratory severity score (SS = mean airway press × FiO2 ) were collected. Twenty-six infants have been enrolled in the ongoing pilot trials. Mean GA and BW were 25.5 ± 1.3 week and 718.3 ± 151.8 g, respectively. Surfactant instillation was tolerated by infants in both trials. Changes in SS, as an index of initial clinical response, are shown as the number of infants with lower SS score/number with same SS score/number with higher SS score compared to the pr-treatment value (mean and range SS): Following treatment, there was an initial decrease in STmin for most infants, indicating improved function. Analysis of concentrations of IL-1α, IL-1β, IL-6, IL-8, TNFα, IL-10, RANTES, MIP-1α, TGF-β1, and VEGF after treatment revealed no significant changes as compared with pretreatment. These preliminary results support the safety of booster surfactant administration in ventilated ELGANS beyond 7 days of age and indicate a favorable initial response in respiratory status. This therapy will be tested for safety and prevention of bronchopulmonary dysplasia in a multicenter, randomized, controlled trial.